Compañía de productos fritos "Bocaos" Ltda. - Angulo Olaya, Myriam (Universidad ESAN. ESAN Ediciones, 1993)
Family business in the food industry managed by five of nine siblings is experiencing declining sales and rising costs. A board of partners must set new directions and policies for the future. The case begins by describing the origin of the problem and then makes a historical account of the development of the company during its 24 years of existence. It exposes the factors and situations that generated its current structure, both internal and its environment. The objective is to awaken in business administration students, particularly in marketing, an analytical and research capacity that will allow them to broaden and deepen their knowledge of topics such as the decision-making process in marketing, new procedures or innovation of existing ones with respect to the management of the elements of the marketing mix, design of strategic plans and marketing programs that guarantee the permanence of an organization. Finally, the case shows the economic, social and political aspects of the environment in which the company operates.

La empresa familiar del sector alimentario, gestionada por cinco de nueve hermanos, está experimentando una caída de las ventas y un aumento de los costes. Una junta de socios debe establecer nuevas direcciones y políticas para el futuro. El caso comienza describiendo el origen del problema para luego hacer un relato histórico del desarrollo de la empresa durante sus 24 años de existencia. Expone los factores y situaciones que generaron su estructura actual, tanto interna como de su entorno. El objetivo es despertar en los estudiantes de administración de empresas, particularmente en marketing, una capacidad analítica y de investigación que les permita ampliar y profundizar sus conocimientos en temas como el proceso de toma de decisiones en marketing, nuevos procedimientos o la innovación de los existentes con respecto al manejo de los elementos del marketing mix, diseño de planes estratégicos y programas de marketing que garanticen la permanencia de una organización. Finalmente, el caso muestra los aspectos económicos, sociales y políticos del entorno en el que opera la empresa.
Keywords: Administrative management; Marketing; Gestión administrativa; Mercadeo; Decision making; Toma de decisiones; https://purl.org/pe-repo/ocde/ford#5.02.04